Let
![y=C_1x+C_2x^3=C_1y_1+C_2y_2](https://tex.z-dn.net/?f=y%3DC_1x%2BC_2x%5E3%3DC_1y_1%2BC_2y_2)
. Then
![y_1](https://tex.z-dn.net/?f=y_1)
and
![y_2](https://tex.z-dn.net/?f=y_2)
are two fundamental, linearly independent solution that satisfy
![f(x,y_1,{y_1}',{y_1}'')=0](https://tex.z-dn.net/?f=f%28x%2Cy_1%2C%7By_1%7D%27%2C%7By_1%7D%27%27%29%3D0)
![f(x,y_2,{y_2}',{y_2}'')=0](https://tex.z-dn.net/?f=f%28x%2Cy_2%2C%7By_2%7D%27%2C%7By_2%7D%27%27%29%3D0)
Note that
![{y_1}'=1](https://tex.z-dn.net/?f=%7By_1%7D%27%3D1)
, so that
![x{y_1}'-y_1=0](https://tex.z-dn.net/?f=x%7By_1%7D%27-y_1%3D0)
. Adding
![y''](https://tex.z-dn.net/?f=y%27%27)
doesn't change this, since
![{y_1}''=0](https://tex.z-dn.net/?f=%7By_1%7D%27%27%3D0)
.
So if we suppose
![f(x,y,y',y'')=y''+xy'-y=0](https://tex.z-dn.net/?f=f%28x%2Cy%2Cy%27%2Cy%27%27%29%3Dy%27%27%2Bxy%27-y%3D0)
then substituting
![y=y_2](https://tex.z-dn.net/?f=y%3Dy_2)
would give
![6x+x(3x^2)-x^3=6x+2x^3\neq0](https://tex.z-dn.net/?f=6x%2Bx%283x%5E2%29-x%5E3%3D6x%2B2x%5E3%5Cneq0)
To make sure everything cancels out, multiply the second degree term by
![-\dfrac{x^2}3](https://tex.z-dn.net/?f=-%5Cdfrac%7Bx%5E2%7D3)
, so that
![f(x,y,y',y'')=-\dfrac{x^2}3y''+xy'-y](https://tex.z-dn.net/?f=f%28x%2Cy%2Cy%27%2Cy%27%27%29%3D-%5Cdfrac%7Bx%5E2%7D3y%27%27%2Bxy%27-y)
Then if
![y=y_1+y_2](https://tex.z-dn.net/?f=y%3Dy_1%2By_2)
, we get
![-\dfrac{x^2}3(0+6x)+x(1+3x^2)-(x+x^3)=-2x^3+x+3x^3-x-x^3=0](https://tex.z-dn.net/?f=-%5Cdfrac%7Bx%5E2%7D3%280%2B6x%29%2Bx%281%2B3x%5E2%29-%28x%2Bx%5E3%29%3D-2x%5E3%2Bx%2B3x%5E3-x-x%5E3%3D0)
as desired. So one possible ODE would be
![-\dfrac{x^2}3y''+xy'-y=0\iff x^2y''-3xy'+3y=0](https://tex.z-dn.net/?f=-%5Cdfrac%7Bx%5E2%7D3y%27%27%2Bxy%27-y%3D0%5Ciff%20x%5E2y%27%27-3xy%27%2B3y%3D0)
(See "Euler-Cauchy equation" for more info)
1 pound of coffee costs 6.95
3.4 pounds will cost 6.95 x 3.4 = 23.63
I Believe it would remain the same unless there is a fee for converting the dollar to yen in the first place.
Answer:
30
Step-by-step explanation:
it counting by 2s but backwards
Answer:
![10^3 = x](https://tex.z-dn.net/?f=%2010%5E3%20%3D%20x%20)
Step-by-step explanation:
![\log_b x = y \Leftrightarrow b^y = x](https://tex.z-dn.net/?f=%20%5Clog_b%20x%20%3D%20y%20%5CLeftrightarrow%20b%5Ey%20%3D%20x%20)
A logarithm is an exponent. For example, the log base 10 of 100 is the exponent you need to raise the base, 10, to get 100. It happens to be 2, so
can be written as ![10^2 = 100](https://tex.z-dn.net/?f=%2010%5E2%20%3D%20100%20)
When you change log form to exponential form, keep these things in mind: The base of the log is also the base of the exponential form. The number that equals the log is the exponent. The number you take the log of is equal to the base raised to the exponent.
Now let's look at your problem.
![\log x = 3](https://tex.z-dn.net/?f=%20%5Clog%20x%20%3D%203%20)
Since no base is shown, the base is 10.
![\log_{10} x = 3](https://tex.z-dn.net/?f=%20%5Clog_%7B10%7D%20x%20%3D%203%20)
The base is 10. The exponent is 3. The base raised to the exponent equals x.
![\log_{10} x = 3 \Leftrightarrow 10^3 = x](https://tex.z-dn.net/?f=%20%5Clog_%7B10%7D%20x%20%3D%203%20%5CLeftrightarrow%2010%5E3%20%3D%20x%20)